Expertise and training of anticipation in goalkeeping: two scoping reviews - Huesmann, K.; Schorer, J.; Büsch, D.; Loffing, F. (Journal of Sports Sciences, 2025)
Anticipation is a crucial perceptual-cognitive skill in goalkeeping. Still, expertise differences in anticipation and its underlying mechanisms as well as effective training of anticipation in goalkeeping have not yet been systematically overviewed nor embedded into a model. Here, we conducted two scoping reviews on (1) expertise in anticipation and (2) training of anticipation in goalkeeping to (a) identify the respective key methodological approaches, (b) understand what distinguishes athletes` anticipation on different expertise levels, (c) apply the knowledge to the Model on Expert Anticipation introduced by Müller and Abernethy and (d) learn how anticipation can be trained. Results from N = 20 studies on expertise in anticipation reveal overall superior anticipation including more effective cue utilisation and, tentatively, visual search behaviour in goalkeepers with higher compared to lower expertise. Thirteen studies on training of anticipation suggest that interventions using explicit, guided discovery or implicit approaches might be used to improve anticipation, each carrying different implications for utilisation. Research focusses mainly on male adult athletes and lab-based standardised penalty situations in soccer and handball with low perception-action coupling in experimental tasks. Key findings, methodological limitations and review-based recommendations for practice and future research are discussed.